2020
DOI: 10.1200/jop.19.00167
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Oral Anticancer Medications After Implementation of an Ambulatory Adherence Program at a Large Urban Academic Hospital

Abstract: PURPOSE: Oral anticancer medications (OAMs) offer convenient administration, reducing the burden of cancer treatment, but create challenges for patients and practitioners. Using data from the Quality Oncology Practice Initiative analysis, a baseline adherence rate of 30% was identified at a large public, academic hospital. To improve OAM adherence, a quality improvement initiative was conducted. METHODS: The aim was to increase OAM patient adherence by 30 percentage points. Through cause-and-effect analysis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Indeed, the presence of adverse efects is strongly associated with poorer adherence [40]. However, a pharmacist-led adherence program can increase the proportion of patients adhering to OAMs [41]. Intentional MMAS-8 scores are also weakly correlated to VAS scores assessing the quality of the information provided by oncologists.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the presence of adverse efects is strongly associated with poorer adherence [40]. However, a pharmacist-led adherence program can increase the proportion of patients adhering to OAMs [41]. Intentional MMAS-8 scores are also weakly correlated to VAS scores assessing the quality of the information provided by oncologists.…”
Section: Discussionmentioning
confidence: 99%
“…This should be performed in coordination with the treating medical oncologist. The involvement of pharmacists has been demonstrated to improve adherence and tolerability 40,41 and increase molecular response to treatment. 42 It also aligns with the position of the International Society of Oncology Pharmacy Practitioners.…”
Section: Importance Of Adherencementioning
confidence: 99%
“…AMBORA trial [ 9 ] suggested that pharmacological/pharmaceutical care significantly reduced severe side effects from oral anticancer drugs compared to those who did not receive such care. Additionally, Marjorie et al [ 12 ] indicated that a pharmacist-led multidisciplinary collaborative approach significantly improved medication adherence to oral anticancer agents. As mentioned above, without the intervention of a multidisciplinary-collaborated team, side effects can be exacerbated, and medication adherence can be reduced.…”
Section: Introductionmentioning
confidence: 99%